Towards elimination of cervical cancer - human papillomavirus (HPV) vaccination and cervical cancer screening in Asian National Cancer Centers Alliance (ANCCA) member countriesSearch strategy and selection criteria - Sok King Ong; Sarah K. Abe; Shyamala Thilagaratnam; Rei Haruyama; Ruchi Pathak; Harindra Jayasekara; Kayo Togawa; Aliza K.C. Bhandari; Abhishek Shankar; Ashrafun Nessa; Uranbolor Jugder; Julyanti Agustina; et al. (Elsevier, 2023)
Summary: About 95% of cervical cancers worldwide are caused by human papillomavirus (HPV). Cervical cancer is preventable and curable if it is detected and treated early. We reviewed the latest national cervical cancer indicators, and barriers to HPV vaccination and cervical cancer screening in 21 Asian National Cancer Centers Alliance (ANCCA) member countries. Half (n = 11, 52%) of the countries have introduced HPV vaccination for girls as part of their national vaccination programme, three countries reported coverage of over 90%. Most ANCCA member countries have cervical cancer screening programmes, only five countries reported screening uptake of over 50%. The barriers to HPV vaccination coverage and cervical cancer screening participation have been identified. Ensuring health service accessibility and affordability for women, addressing sociocultural barriers, and strengthening the healthcare system and continuum of care are essential to increase HPV vaccination and cervical cancer screening coverage.